Assessment Of Arabic Writing Skills In Differentiated Learning Based On Project-Based Learning - Salsabila, Novita Maula; Baroroh, R Umi (Ijaz Arabi Journal of Arabic Learning, 2024)
Each learner is unique and has a diverse background and abilities. Every learner has the right to receive learning according to their way of learning. Differentiated learning is one of the solutions to fulfill this diversity. The process of differentiating a series of learning processes, including assessment, is carried out to answer each learner's learning needs, styles, or interests. This research aims to create an assessment innovation in differentiated learning based on project-based learning, especially in writing skills. The method used in this research is a literature study with a descriptive qualitative approach. The result of this study is that the assessment of writing skills in project-based learning differentiated learning can be done through product or project assessment that is adjusted to students' readiness and ability.